Dispersion modelling in rivers for water sources protection, based on tracer experiments : case studies. - Duarte, António A. L. Sampaio (2008)
Judicious selection of mathematical models for application in a specific river basin management can mitigate prediction uncertainty. Therefore, intervention times will be established with better reliability and alarm systems could efficiently protect the aquatic ecosystems and the public health. The main purpose of this paper is to evaluate the performance of river water systems dispersion modelling, based on tracer experiments data for calibration and validation. The present work describes the methodology used in the monitoring programs, which were carried out using tracer injection (rhodamine WT) to determine the in situ river water dispersion behaviour and the mathematical models applied to simulate different water quality management scenarios on each reach of the three rivers studied: Mondego, Douro and Tagus rivers. The models were calibrated in order to produce operational tools to estimate the probabilistic arrival/peak/recession times, and reminiscent substance concentrations to define, for example, how long water intake need to be suspended after a pollutant spill. The good correlation between experimental data and simulation results allows us to conclude that the applied models showed enough accuracy to describe and predict conservative pollutant transport under different hydrodynamic scenarios, validating this methodology to support the environmental impact assessment of pollutant loads, in order to select the best water sources protection practices.